(untitled) (Acta Entomologica Serbica, 2023)
Ephestia kuehniella is an important cereal pest and Habrobracon hebetor is its efficient biocontrol control worldwide. The enzyme phenoloxidase is one of the major components of the insect immune system. This enzyme catalyzes the quinones and other reactive intermediates to reduce parasitoid invasion. In this study, the effects of five commercial insecticides in Iran on the parasitism percentage of H. hebetor and on the activation of phenoloxidase in the hemolymph of host larvae as an important indicator were investigated. The results showed that the percentage of parasitism was significantly lower in insecticide treatments compared to the control (F5, 42= 6.471). There were significant differences in total protein content among the control and insecticides treatments, as well as in the phenoloxidase activity in the host larvae. Accordingly, the highest activity was in the control (0.3924±0092 μM/min/mg protein) and the lowest when larvae were treated with propargite (0.1927±0.0169 μM/min/mg protein). The results confirmed that the insecticides palizin and buprofezin do not have serious negative effects on H. hebetor parasitism when combined in integrated pest management.